The coagulation impact of 50% epoxidised natural rubber chain in ethylene carbonate-plasticized solid electrolytes - Latif, Famiza (John Wiley & Sons Ltd., 2009)
In this research, thin, soft and flexible free standing films can be obtained from poly (methyl methacrylate) (PMMA)/50% epoxidised natural rubber (ENR 50)/lithium triflate (LiCF(3)SO(3)) blends. However, phase separation is observed on the surface of the films which indicates that the blending is not homogeneous. The blend became more homogeneous when ethylene carbonate (EC) plasticizer is introduced into the blend system. However, the anti-plasticization effect of EC on ENR 50 occurs at lower concentration of EC at which the rubber became coagulated due to immiscibility of the rubber with EC plasticizer during solution casting. These ENR 50 coagulates can be observed as large solid structures in the Field Emission Scanning Electron Microscope (FESEM) micrographs of the EC-plasticized rubber-based electrolytes. The presence of these coagulates, hinder the migration of lithium ions in the system and also trap the lithium ions within the coil. This in turn reduced the number of free lithium ions that contribute to the ionic conduction. As a result, the conductivity of the un-plasticized PMMA/ENR 50/LiCF(3)SO(3) film dropped drastically by two orders of magnitude.